The Trimodality PET/CT–MRI (3.0 T) System with a Dedicated Shuttle Detects Local Recurrence in a Case Classified as Indeterminate by Means of PSMA PET/CT Alone at Prostatic Fossa - dos Santos Loureiro, Gerardo Gabriel; Gambini González, Juan Pablo; Parodi, Martin Rodriguez; Alonso Núñez, Omar (World Journal of Nuclear Medicine, 2025)
In the following case study, we evaluate a prostate cancer patient with persistent biochemical relapse and negative conventional imaging. Following interdisciplinary team discussion, it is decided to assess the patient by a 11C-Choline and 68Ga-PSMA positron emission tomography/computed tomography (PET/CT) scan. Notably, doubtful findings due to physiological urinary activity in the 68Ga-PSMA-11 PET/CT scan were clarified with PET/CT–magnetic resonance imaging (MRI) images. The added value of the trimodality PET/CT–MRI system was very useful in detecting recurrence in a case classified as indeterminate by means of PET/CT alone at prostatic fossa.
Keywords: PET/CT–MRI; prostate cancer; 68Ga-PSMA-11; biochemical recurrence